Odpowiedzi

Najlepsza Odpowiedź!
2010-03-24T20:33:45+01:00
A) 2(a - 2b) - 7 (3a - b) = 2a-4b-21a+7b = 2a-21a-4b+7b=-19a+3b
b) 5(x - y) + 2(4x + 2y) - 3(2x + y) = 5x-5y+8x+4y-6x-3y= 5x+8x-6x-5y+4y-3y=7x-4y
c) 5(x + 2y - 3z) - 2(4x - 3y + z) = 5x+10y-15z-8x+6y-2z = -3x+16y -17z
d) -(k - m -n) + 2(k + 2m + 3n) - kmn = -k+m+n+2k+4m+6n-kmn=k+5m+7n-kmn
e) 2p (3p -2r) + 3r(p-2r) = 6p²-4pr+3pr-6r² = 6p²-6r²-1pr
57 1 57
2010-03-24T20:37:30+01:00
A) 2(a - 2b) - 7 (3a - b) -2a - 4b=
2a-4b-21a+7b-2a-4b=
-21a-b

b) 5(x - y) + 2(4x + 2y) - 3(2x + y) =
5x-5y+8x+4y-6x-3y=
7x-4y

c) 5(x + 2y - 3z) - 2(4x - 3y + z)
5x+10y-15z-8x+6y-2z=
-3x+16y-17z

d) -(k - m -n) + 2(k + 2m + 3n) - kmn =
-k+m+n+2k+4m+6n-kmn=
k+5m+7n-kmn

e) 2p (3p -2r) + 3r(p-2r) =
6p²-4pr+3rp-6r²=
6p²-pr-6r²

6 3 6
2010-03-24T20:39:53+01:00
A) 2(a - 2b) - 7 (3a - b) +2a - 4b=
2a-4b-21a+7b+2a-4b+2a-4b=-15a-5b
b)5(x - y)+2(4x+2y)-3(2x+y)=5x-5y+8x+4y-6x-3y=7x-4y
c)5(x + 2y - 3z) - 2(4x - 3y + z)=5x+10y-15z-8x+6y-2z=-3x+16y-17z
d)-(k-m-n)+2(k+2m+3n)-kmn=-k+m+n+2k+4m+6n-kmn=k+5m+7n-kmn
e)2p(3p-2r)+3r(p-2r)=3p²-4pr+3rp-6r²=6p²-4pr+3rp-6r²


5 2 5